2007
DOI: 10.1111/j.1399-6576.2007.01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of six risk scores for outcome after surgical repair of hip fracture in elderly patients

Abstract: A simple index such as the RISK-VAS scale was the best predictor of serious post-operative complications. The functional level before the fracture, measured with the Barthel index, had a major influence on the ambulation recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 41 publications
6
59
0
10
Order By: Relevance
“…Our analysis of outcome in the different risk bands revealed that calibration was poor independent of method to predict mortality. Moreover, ROC analysis in the present study suggests poor discrimination and is very similar to the area under ROC curve reported for hip fracture patients in previous studies (0.62‐0.68)9, 12, 13 with the exception of a single study reporting an area under the ROC curve of 0.83 14. As suggested above, a potential explanation for the differing results in the studies targeting hip fracture patients is the method used to calculate risk bands.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our analysis of outcome in the different risk bands revealed that calibration was poor independent of method to predict mortality. Moreover, ROC analysis in the present study suggests poor discrimination and is very similar to the area under ROC curve reported for hip fracture patients in previous studies (0.62‐0.68)9, 12, 13 with the exception of a single study reporting an area under the ROC curve of 0.83 14. As suggested above, a potential explanation for the differing results in the studies targeting hip fracture patients is the method used to calculate risk bands.…”
Section: Discussionsupporting
confidence: 88%
“…The Physiological and Operative Severity Score for the enUmeration of mortality and morbidity (POSSUM) score is a commonly used scoring system for perioperative risks which takes into account both the preoperative physiological status and the characteristics of the surgical procedure 8. The POSSUM score has been investigated in hip fracture patients in a number of studies with variable results with regard to calibration and discrimination 9, 10, 11, 12, 13, 14. Performance in a Scandinavian setting is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Different tools to estimate perioperative risk of elderly patients with hip fractures [11] have been described. For our model, we conducted a literature review using PubMed searching the terms ''hip fracture mortality risk prediction'', and identified studies which specifically described two critical factors: (1) odds ratio (OR) of mortality as a function of risk stratification, and (2) change in length of stay as a function of risk stratification.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…There is some controversy between the value of the ASA grade and predicting mortality in the literature [5] [13] [14]. Some authors support the link between ASA score and mortality [15]- [20] The Donati score is a non-specific general surgical and orthopaedic 4-item score using age range, ASA, surgical severity, and urgency of surgery to calculate mortality risk.…”
Section: Discussionmentioning
confidence: 99%